PENGARUH PENGGUNAAN MODE ALTITUDE MODE 2 DAN MODE 3 SEPEDA MOTOR BEAT 2018 FI PADA KETINGGIAN 0-1000 MDPL TERHADAP EMISI GAS BUANG - Prasetyo, Imam; Budiyono; Anam, Khoirul (Surya Teknika : Jurnal Ilmiah Teknik Mesin, 2022)
In testing the effect of using altitude mode 2 and mode 3 Beat Fi motorcycles at an altitude of 0-1000 MDPL on exhaust emissions, this study uses descriptive data analysis methods. The results of the HC test in Mode 1 get the highest results at RPM 3000, which is 481 ppm, while the lowest results at RPM 1000 are 229 ppm. In Mode 2, the highest result is obtained at RPM 3000, which is 1074 ppm, while the lowest result is at RPM 1500, which is 349 ppm. In Mode 3, the highest result is obtained at RPM 2500, which is 1052 ppm while the lowest result is at RPM 1500, which is 468 ppm, while in CO testing in Mode 1, the highest result is obtained at RPM 3000, which is 5.27%, while the lowest result is at RPM 1000, which is 1, 04%. In Mode 2, the highest result is obtained at RPM 3000, which is 6.71%, while the lowest result is at RPM 1000, which is 2.37%. In Mode 3, the highest result is obtained at RPM 3000, which is 8.16%, while the lowest result is at RPM 1500, which is 2.96. From this explanation, it can be concluded that the effect of using mode 2 and mode 3 at an altitude of 0 - 1000 MDPL in mode 2 is that the higher the rpm, the higher the HC and CO levels, while in the higher rpm mode, the HC and CO levels decrease at 3000 rpm.Keywords: Altitude Mode, Exhaust Emissions